Metal–Organic Framework‐Based Electrocatalysts for CO2 Reduction. Issue 5 (12th September 2021) - Shah, Syed Shoaib Ahmad; Najam, Tayyaba; Wen, Ming; Zang, Shuang-Quan; Waseem, Amir; Jiang, Hai-Long
Abstract : The increasing concentration of CO2 is alarming for modern society and the reduction of CO2 into valuable products is the unique solution. Metal–organic frameworks (MOFs), constructed by organic linkers interconnected with metal (oxide) nodes, with high porosity and large surface area, have become an emerging class of electrocatalysts for reduction of CO2 . Herein, the recent advancements in MOF‐based electrocatalysts for the reduction of CO2, abridged the recent strategies to enhance the performance are summarized and the structure–activity relationship is discussed to provide a comprehensive route for the rational design of novel catalysts. Moreover, the specially focused aspect is to summarize recent strategies of structure tuning, manipulating the electronic structure and enhancing the active site density to well exposed single‐atom active sites. In addition, some demerits and proposed future perspectives are also discussed. Abstract : The recent progress in metal–organic framework (MOF)‐based electrocatalysts for CO2 reduction is summarized from synthetic strategies to enhanced performance. The discussions on structure–activity relationship provide important insights into the rational design and synthesis of related catalysts with well exposed active sites. In addition, some demerits and proposed future perspectives are also discussed.